Navigating uncertain waters: 12 tips for medical department social media engagement under shifting platform landscapes [version 3; peer review: 2 approved, 1 approved with reservations, 1 not approved] - Zachary Van Roy; Jasmine R. Marcelin; Kelly A. Cawcutt (MedEdPublish)
Social media has revolutionized how society receives and transmits information in the digital age, including healthcare. While the future of social media platforms remains uncertain, the benefits of social media for healthcare organizations, departments, and divisions are clear when compared to traditional communication methods, including improved recruitment efforts, increased promotion of faculty work, rapid dissemination of information and education innovations, and accelerated professional networking. Consequently, preferred platforms may shift but the benefits of social media likely cement it, in one form or another, in medical education and society at large. The strategic development of a social media presence at the department level can be opaque and overwhelming amidst varying mediums, yet the benefits of use have never been more important. Here, we present 12 tips for developing a successful social media presence as a healthcare department, addressing the creation of a purposeful social media strategy and crucial considerations for any platform, current or future, at all levels of development.